Prevalence and correlates of multimorbidity among patients attending AYUSH primary care settings in Delhi-National Capital Region, India - Roja Varanasi; Abhinav Sinha; Debadatta Nayak; Raj K. Manchanda; Rajiv Janardhanan; Simran Tandon; Sanghamitra Pati (BMC, 2023)
Abstract Introduction India has a multifaceted healthcare system and recognizes complementary and alternative systems of medicine (AYUSH) that cater to the healthcare needs of people. Multimorbidity requires frequent visits to physicians and long-term use of medications, due to which people tend to prefer AYUSH systems as they provide holistic patient-centered treatment. Hence, we aimed to estimate the prevalence of multimorbidity and assess its correlates among patients attending AYUSH primary care clinics in Delhi. Methods A cross-sectional study was conducted among 943 patients aged ≥ 18 years attending various AYUSH primary care clinics in Delhi from September 2021 to February 2022, employing a stratified random sampling technique. Descriptive statistics such as frequency and proportion were used to report the prevalence of multimorbidity (two or more chronic conditions in an individual out of the 33 conditions listed as per the Multimorbidity Assessment Questionnaire for Primary Care). A multivariable logistic regression assessed the association between various socio-demographic characteristics and multimorbidity, presented as an adjusted odds ratio (AOR) with a 95% confidence interval (CI). Results The prevalence of diabetes (14.7%) was found to be the highest (out of all included chronic conditions) among the patients attending various AYUSH primary care settings. The overall prevalence of multimorbidity was observed to be around 39.4%. We observed a higher likelihood of having multimorbidity among participants aged ≥ 70 years [AOR: 9.19 (95% CI: 3.75-22.54)], females [AOR: 1.57 (95% CI: 1.04-2.37)], and middle class [AOR: 2.23 (95% CI: 1.45-3.43)]. Conclusion Multimorbidity was evidently prevalent across AYUSH primary care settings, which cannot be overlooked. The results suggest behavioral change communication may be aimed at older individuals, females, and the middle class.